Differential-based biosensor arrays for detecting carcinogens in heat-processed foods / Wong Siew Fang - Wong , Siew Fang (2021)
Food contamination is a severe issue owing to the large concentration of chemicals in foods that causes serious health problems. Protecting public health and preventing contaminated foods are a high priority. Foodborne chloropropanols and amides, specifically 3-chloropropane-1,2-diol (3-MCPD) and acrylamide, are vitally important for food safety and food security, as they are the most popular food toxicants and suspected human carcinogens. Chloropropanols are challenging analytes because of the scarcity of functional group diversity and difficulty in aiming the hydroxyl groups in aqueous conditions. In addition, due to their small molecular size, time-consuming, labor-intensive, and costly derivatization methods are often required for acquiring desirable chromatographic patterns and enhancing the detectability and stability of the analytes. Similarly, an intricate sample pretreatment procedures and requirement for sophisticated instrumentation in the existing analytical approaches unfortunately render difficulties in the rapid, simplistic, on-the-spot sensitive determination of acrylamide. Therefore, achieving physical chromatographic determination is challenging. Apart from chromatographic techniques, electrochemical method with higher detection limit and lower sensitivity hinders the detection of trace concentrations of 3-MCPD and acrylamide in foods. Considering these potential limitations, an array-based differential optical biosensing methods were proposed. The concept of differential sensing is primarily based on fingerprint patterns generated from the interactions between the analytes and the cross-reactive receptors with multifarious binding affinities, thus facilitating the detection of small-molecule analytes. As compared to conventional chemosensor, differential biosensor array has the added advantage of precluding the strenuous procedures for developing a highly specific receptors in detecting small analytes. Employing serum albumins, ascorbic acid, and PRODAN, a differential-based fluorescent biosensor array was developed to differentiate and detect chloropropanols. The sensor array integrated with linear discriminant analysis effectively differentiated four chloropropanols based on the number of hydroxyl groups and their isomerism properties, even at ultra-low concentration (5 nM). The sensor array was then applied for chloropropanols quantification and differentiation in synthetic soy sauce samples. Leave-one-out cross-validation analysis revealed 100% accurate classification for all experiments. In contrast, exploring molecular interactions at the bio-nano interfaces facilitated the development of array-based detection system with gold nanoparticles as a colorimetric probe. A combination of distinct proteins as cross-reactive bioreceptors and the subsequent fine-tuning of the protein surface coverage on the gold nanosurface with dithiothreitol resulted in a differential-based colorimetric nanobiosensor array for the detection, differentiation, and quantification of acrylamide and six analogues. Using the principal component analysis and hierarchical cluster analysis, acrylamide and six analogues were successfully detected and discriminated based on their amine subgroups, IARC carcinogen classifications, and food additive types, at concentrations as low as 500 pM. Furthermore, the sensor array has the capability to identify and differentiate non-targeted analytes by the types of sweeteners and food ingredients, apart from distinguishing and quantifying individual analytes and mixtures of them in the coffee samples. Considering the benefits of high sensitivity and simple design, the differential-based biosensor arrays show great promise for food safety monitoring in the food and beverage industry.